Analysis and Study on the Bearing Capacity of Socketed Piles in StronglyWeathered Argillaceous Dolomite in Guiyang - CAI Hang; MU Rui; HUANG Zhihong; XIAO Lina; CHEN Xu; LIU Jiuhong (Renmin Zhujiang)
In Guiyang, the tip of socketed pile is often placed on a complete or relativelycomplete rock foundation, and the bearing capacity of socketed pile is often calculated as end-bearing pile. This paper takes the socketed pile in strongly weathered argillaceous dolomite in aprojectin Guiyang as the research object, analyzes the vertical bearing capacity, side resistanceand tip resistance of socketed pile in strongly weathered argillaceous dolomite through self-balanced static load test of foundation pile, and discusses the bearing characteristics ofsocketed pile under such geological condition.The results show that: ①The measured Q-s curve oftest pile conforms to the test rules; ②The axial force of pile is distributed linearly; ③Theaxial force of socketed section changes obviously with the increase of load; ④The verticalbearing capacity of socketed pile instrongly weathered argillaceous dolomite is undertaken by tipresistance and side resistance, which can provide reference for similar projects.